Noise exposure and auditory thresholds of German airline pilots: a cross-sectional study. Issue 5 (30th May 2017) - Müller, Reinhard; Schneider, Joachim
Abstract : Objective: The cockpit workplace of airline pilots is a noisy environment. This study examines the hearing thresholds of pilots with respect to ambient noise and communication sound. Methods: The hearing of 487 German pilots was analysed by audiometry in the frequency range of 125 Hz–16 kHz in varying age groups. Cockpit noise (free-field) data and communication sound (acoustic manikin) measurements were evaluated. Results: The ambient noise levels in cockpits were found to be between 74 and 80 dB(A), and the sound pressure levels under the headset were found to be between 84 and 88 dB(A). The left–right threshold differences at 3, 4 and 6 kHz show evidence of impaired hearing at the left ear, which worsens by age. In the age groups <40/≥40 years the mean differences at 3 kHz are 2/3 dB, at 4 kHz 2/4 dB and at 6 kHz 1/6 dB. In the pilot group which used mostly the left ear for communication tasks (43 of 45 are in the older age group) the mean difference at 3 kHz is 6 dB, at 4 kHz 7 dB and at 6 kHz 10 dB. The pilots who used the headset only at the right ear also show worse hearing at the left ear of 2 dB at 3 kHz, 3 dB at 4 kHz and at 6 kHz. The frequency-corrected exposure levels under the headset are 7–11 dB(A) higher than the ambient noise with an averaged signal-to-noise ratio for communication of about 10 dB(A). Conclusions: The left ear seems to be more susceptible to hearing loss than the right ear. Active noise reduction systems allow for a reduced sound level for the communication signal below the upper exposure action value of 85 dB(A) and allow for a more relaxed working environment for pilots.